Disparities in the contraceptive use among currently married women in Muslim densely populated States of India: An evidence from the nationally representative survey. (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The rationalizations for low use of contraception and high fertility among Muslims compared to other religious group in India are highly controversial. The study was aimed to explain to what extent differences in the use of contraception exist among the religious groups and also examine its associated factors in the Muslim populated States in the country.Methods: The third round of District Level Household and Facility Survey (DLHS-3) was used to accomplish our objectives. Bivariate analysis was used to show the religion wise distribution of limiting, spacing and traditional methods of contraceptive use in relation to socio-economic characteristics. The multivariate logistic regression was also employed to estimate the odds ratio (95% CI) for contraceptive use. SPSS 20.0 version and Arc GIS 10.0 software were employed to carry out the analyses.Results: The study found that the prevalence of limiting contraceptive use was comparatively much lower among Muslims (19.9%) than Non-Muslims (39.3%). In comparison to Non-Muslims, Muslims used 3.5 percentage points and 2.6 percentage points spacing and traditional methods of contraception respectively. The Muslims women from Assam (3.4%), Uttar Pradesh (4.4%) and Bihar (8.3%) reported low use of limiting contraceptive methods as compared to other Muslim populated States. The highest difference in the limiting method was observed in Bihar (21 percentage points) and followed by West Bengal (19 percentage points) between Muslim and Non-Muslim. The level of education and place of residence appeared as the main explaining factors of family planning in the study.Conclusion: The study concluded that the significant inequalities exist among Muslims and Non-Muslims concerning the current use of limiting methods. The policy design and programmes should make on rural, uneducated women to take into account the inequalities in the contraceptive use.